Metacognitive function in young adults is impacted by physical activity, diet, and sleep patterns. - G Kyle Gooderham; Todd C Handy (PLoS ONE)
Our cognitive capacities like working memory and attention are known to systematically vary over time with our physical activity levels, dietary choices, and sleep patterns. However, whether our metacognitive capacities--such as our strategic use and optimization of cognitive resources--show a similar relationship with these key lifestyle factors remains unknown. Here we addressed this question in healthy young adults by examining if physical activity, diet, and sleep patterns were predictive of self-reported metacognitive status. Participants completed a set of validated surveys assessing these lifestyle factors over the past week to month, as well as three measures of metacognition. Using multiple regression and exploratory factor analyses we identified four clusters of metacognitive processes that are sensitive to lifestyle behaviours. Specifically, knowledge of and offline regulation of cognition is linked with physical activity, on-line cognitive regulation is related to diet, and metacognitive worry is associated with sleep behaviours. These findings suggest that lifestyle behaviours do not just affect objective cognitive functioning, but also the meta-level processes we use to monitor our cognitive performance and exert strategic control over our cognitive resources.